Association of polychlorinated biphenyls with vitamin D in female subjects - Butler, Alexandra E.; Brennan, Edwina; Drage, Daniel S.; Sathyapalan, Thozhukat; Atkin, Stephen L. (Environmental research, 2023)
Polychlorinated biphenyls (PCBs) are known endocrine disrupters. A potentially causal association of PCBs with vitamin D has been reported. Higher body mass index (BMI) is associated with lower PCB levels whilst the strongest association of PCBs with BMI is in non-obese individuals. Therefore, this study examined the association of PCBs with vitamin D3 (25(OH)D3) and the active 1,25-dihydrovitamin D3 (1,25(OH)2D3) in a cohort of non-obese women. 58 female participants (age 31.9 ± 4.6 years; BMI 25.7 ± 3.7 kg/m2) had seven indicator PCBs [PCB28, PCB52, PCB101, PCB118, PCB138, PCB153 and PCB180] measured using high resolution gas chromatography, with total PCB level calculated. 25(OH)D3 and 1,25(OH)2D3 levels were determined by isotope-dilution liquid chromatography tandem mass spectrometry. In this cohort, vitamin D3 (25(OH)D3) and 1,25(OH)2D3 levels were 50.7 ± 25.3 nmol/L and 0.05 ± 0.02 ng/ml, respectively. Of those, 28 had vitamin D deficiency [25(OH)D3 level <20 ng/ml (<50nmol/)]. Total PCBs correlated positively with total group 25(OH)D3 (r = 0.22, p = 0.04) as did PCB118 (r = 0.25, p = 0.03). Total PCBs did not correlate with total group 1,25(OH)2D3; however, PCB180 did correlate positively with 1,25(OH)2D3 (r = 0.34, p = 0.03) as did PCB153 (r = 0.33, p < 0.03), with PCB 28 correlating negatively (r = −0.29, p < 0.04). In the vitamin D deficient subgroup, total PCBs, PCB153 and PCB180 positively correlated with 25(OH)D3 (p < 0.05). Multilinear regression analysis indicated all associations could be accounted for by BMI. Though certain PCBs associated with 25(OH)D3 and 1,25(OH)2D3, all associations could be accounted for by BMI. This study therefore indicates that the deleterious effects from PCB accumulation are not mediated by effects on 25(OH)D3 or 1,25(OH)2D3. •Polychlorinated biphenyls (PCBs) are known endocrine disrupters.•A potentially causal association of PCBs with vitamin D has been reported.•In these non-obese females, certain PCBs associated with vitamin D3.•All associations could be accounted for by body mass index.•Deleterious effects of PCB accumulation are not mediated by effects on vitamin D3.